An audit of the Day-of-Surgery Cancellation of Scheduled Surgical Procedures in Sagamu, Nigeria - Fatungase OM; Sogei OA; Nwokoro CC; Oyelekan AA (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2016)
Background: Timely performance of scheduled surgical procedures may be an indirect method of assessing the quality of surgical services in a hospital. Objective: This study aimed to determine the rate and the reasons for day-of-surgery cancellation of elective surgical procedures. Methods: A prospective study was conducted at the Olabisi Onabanjo University Teaching Hospital, Sagamu, Nigeria to audit the type of surgery and the reasons for the cancellation of procedure among patients scheduled for elective surgical procedures. Results: A total of 1,324 patients were scheduled for elective surgeries during the period of audit and 268 (20.2%) were cancelled on the day of surgery. One hundred and seventy-four of the 268 (65.0%) cancellations were avoidable while 94 (35.0%) cancellations were unavoidable. The reasons for the cancellation of surgeries included patient-related factors (35.0%), unfavourable pre-operative clinical evaluation (31.0%), facility-based factors (28.0%) and surgeon-related factors (6.7%). Conclusion: The day-of-surgery cancellation rate was 20.2%, and the three leading causes of cancellation of elective surgeries in Sagamu included patient-related factors, unfavourable pre-operative clinical evaluation and inadequacies of hospital resources.